2002
DOI: 10.1002/joc.780
|View full text |Cite
|
Sign up to set email alerts
|

The climatology of sea breezes on Sardinia

Abstract: Hourly wind speed and direction data from 12 coastline stations on Sardinia, Italy, are analysed in order to characterize sea breezes in the region. A set of criteria based on the diurnal reversal of wind direction, and the thermal gradient necessary to drive the circulation, is used to identify sea breeze days. Statistics are presented that describe the occurrence, duration, and strength of the sea breezes. On a stationwide basis, sea breezes are most frequent in the summer months (May-August), when they appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 18 publications
(28 reference statements)
6
115
0
2
Order By: Relevance
“…2 (left) and 4a show that midnight points (near the X symbols) and some midafternoon points tend to stagnate, with the former defining a tighter cluster than the latter. This finding demonstrates that the rotation rate changes over the course of a day, as reported in previous studies (e.g., Staley 1957;Furberg et al 2002). By definition, such an asymmetric rotation rate cannot be explained solely in terms of the diurnal component.…”
Section: Rotation Ratesupporting
confidence: 86%
See 1 more Smart Citation
“…2 (left) and 4a show that midnight points (near the X symbols) and some midafternoon points tend to stagnate, with the former defining a tighter cluster than the latter. This finding demonstrates that the rotation rate changes over the course of a day, as reported in previous studies (e.g., Staley 1957;Furberg et al 2002). By definition, such an asymmetric rotation rate cannot be explained solely in terms of the diurnal component.…”
Section: Rotation Ratesupporting
confidence: 86%
“…According to Haurwitz's (1947) theory, the rotation direction should always be clockwise, and the rotation rate should be the same between during the daytime and during the nighttime; however, subsequent observational studies have reported anticlockwise rotation directions (e.g., Mori 1982;Furberg et al 2002) and different rotation rates from those predicted by Haurwitz (e.g., Neumann 1977;Zhong and Takle 1992;Furberg et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Our analysis is based on sea breeze detection criteria developed in Steyn and Faulkner (1986) and Furberg et al (2002). Steyn and Faulkner (1986) encountered major difficulties in establishing the criteria for determining sea breeze and non-sea breeze days, mainly due to the difficulty of separating local, thermally driven circulations from synoptic-scale circulations.…”
Section: Discussionmentioning
confidence: 99%
“…Climatological studies of sea breeze are found in literature for many regions throughout the world such as Lower Fraser Valley, B.C. (Steyn and Faulkner, 1986), St. Johns, Newfoundland (Banfield, 1991), West Coast of Sweden (Gustavsson et al, 1995;Borne et al, 1998), Sardinia (Furberg et al, 2002), Northern Adriatic (Maja, 2003), Arabian Gulf region (Eager et al, 2008), Alicante (Azorin-Molina et al, 2009), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation